Activation of STING Based on Its Structural Features - Hussain, Behzad; Xie, Yufeng; Jabeen, Uzma; Lu, Defen; Yang, Bo; Wu, Changxin; Shang, Guijun (Frontiers in Immunology, 2022)
The cGAS-cGAMP-STING pathway is an important innate immune signaling cascade responsible for the sensing of abnormal cytosolic double-stranded DNA (dsDNA), which is a hallmark of viral infection or cancers. Recently, tremendous progress has been made in the understanding of STING activation mechanism from various aspects. In this review, the molecular mechanism of activation of STING protein based on its structural features is briefly discussed. The underlying molecular mechanism of STING activation will enable us to develop novel therapeutics to treat STING-associated diseases and understand how STING has evolved to eliminate infection and maintain immune homeostasis in innate immunity.